Responsibilities of The Regional Representative Council of North Aceh District In Order to Implement Budgetary Functions Regarding The Regional Revenue and Expenditure Budget (APBD) - Zaini, Muhd; H, Harun; A, Arnita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to examine the North Aceh Regency Regional People's Representative Council in order to carry out its Budget Function towards the APBD, what obstacles the North Aceh Regency Regional People's Representative Council faces in carrying out its Budget Function towards the APBD and the efforts made by the Regency Regional People's Representative Council North Aceh if there are obstacles in carrying out its duties as a Budget Function for the APBD. The Regional People's Representative Council is the regional government administrator whose task is to voice the aspirations of the community and act on behalf of the people in the legislative field. The preparation of the APBD is based on a plan that has been determined in advance regarding the programs and activities that will be implemented by the regional government. The APBD preparation process begins with the preparation of the General Budget Policy draft and the Temporary Budget Priorities and Ceiling documents. The process of establishing a new Regional Budget Regulation will be carried out if it has been declared not to conflict with the public interest and higher regulations by the Minister of Home Affairs or the Governor. It is hoped that this study will be able to provide benefits both scientifically, namely in the realm of legal studies, both practically and academically. The research method used in this research is a type of qualitative research using a normative empirical approach. This approach is basically a combination of a normative legal approach with the addition of various empirical elements. There are three legal materials used by the author, namely primary legal materials, secondary and tertiary materials. The results of this analysis and research conclude that the Regional People's Representative Council of North Aceh Regency is the party responsible for APBD accountability and does not comply with the provisions regarding the preparation of the APBD in the legislation. Because when preparing the APBD, one of the bodies in the DPRD is the Budget Body whose task is to discuss together the North Aceh Regency APBD until early December or the final deadline for determining the North Aceh Regency APBD based on the provisions of the law.